Yellowing mechanisms of epoxy and vinyl ester resins under thermal, UV and natural aging conditions and protection methods. (October 2022) - Wu, Chao; Meng, Bing Chen; Tam, Lik-ho; He, Li
Abstract: Polymer resins have yellowing issue when subjected to elevated temperatures or UV exposure, which limit their applications in color-sensitive fields. This paper presents an experimental study on the yellowing mechanisms of epoxy and vinyl ester resins under thermal, UV and natural aging conditions. Anti-yellowing methods including air isolation, antioxidant, UV absorber are selected and their effectiveness is assessed. The resins before/and after aging are characterized to analyze their yellowing index, surface morphology, weight loss, mechanical properties (i.e. modulus and Vickers hardness), glass transition temperature and FT-IR spectra. The yellowing mechanisms and the influencing factors are discussed. It is found that the resin yellowing is a result of radical oxidation reaction due to aging, which forms chromophores such as carbonyl groups, double bonds and conjugated structures. Vinyl ester has better yellowing resistance than epoxy. Antioxidant and UV absorber are not effective in terms of anti-yellowing effect, but air isolation has the best performance to slow down the yellowing process. Yellowing in natural environment can be more complicated due to other factors like moisture, wet-dry cycles etc. This study provides an experimental evidence for the study of yellowing mechanisms of polymer resins. Highlights: Yellowing mechanisms of epoxy and vinyl ester resins under thermal, UV and natural aging conditions are investigated. The effectiveness of anti-yellowing methods is assessed including air isolation, antioxidant and UV absorber. It is found that the resin yellowing is a result of radical oxidation reaction which forms chromophores. Vinyl ester has better yellowing resistance than epoxy. Antioxidant and UV absorber are not effective in terms of anti-yellowing effect while air isolation has the best performance.